How full is your glass? Portion sizes of wine, fortified wine and straight spirits at home in the Netherlands. Issue 10 (26th March 2019) - de Beukelaar, Myrthe FA; Janse, Marion L; Sierksma, Aafje; Feskens, Edith JM; de Vries, Jeanne HM
Abstract: Objective: Alcohol consumption may be wrongly estimated because of inaccurate information on actual portion sizes. We compared portion sizes of wine, fortified wine and straight spirits poured at home with the Dutch standard drink sizes. Design: Participants measured portion sizes of wine, fortified wine and straight spirits at home up to a maximum of three times and reported these via an online survey. Average portion sizes (in millilitres) were compared with the Dutch standard drink sizes. Portion sizes were compared between subgroups of gender, age, BMI and level of education, and for different glass types. Setting: Wageningen and surroundings, the Netherlands. Participants: Adults ( N 201) living in the Netherlands and consuming wine and/or straight spirits at home at least once per week. Results: Participants poured on average 129·4 ml white wine and 131·7 ml red wine, which is significantly more than the standard of 100 ml. For fortified wine, the average poured amount was 94·0 ml, significantly more than the standard of 50 ml; also for straight spirits the poured amount was significantly more than the standard (47·0 v . 35 ml). Conclusions: Participants' portion sizes of wine, fortified wine and straight spirits poured at home were on average larger than the Dutch standard drink sizes. This suggests that at-home alcohol consumption in the Netherlands is underestimated.